Pengaruh Disiplin Kerja Dan Lingkungan Kerja Fisik Terhadap Kinerja Karyawan Pada PT. Tunas Lima Warna - Muhammad Rifki Allamsyah; Nindie Ellesia (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
The purpose of this research is to determine the influence of work discipline and the physical work environment on the performance of PT employees. Tunas Lima Warna, South Tangerang. This type of research is a type of quantitative research using data collection techniques using observation, questionnaires, score measurement and documentation. The population in this research is all employees of PT. Tunas Lima Warna, South Tangerang, namely 64 employees, the sampling technique used saturated sampling, so all employees of PT. Tunas Lima Warna, South Tangerang was used as a sample for this research, namely 64 employees. The data analysis techniques in this research are descriptive analysis, research instrument test, classical assumption test, multiple linear regression test, correlation coefficient test, coefficient of determination test, as well as t test and F test using SPSS version 26 tools. The results of this study show that There is an influence between Work Discipline (X1) on Employee Performance (Y) at PT. Tunas Lima Warna, South Tangerang, this can be seen from the results of the t test with a value of tcount > ttable (13.212 > 1.999), this is also proven by the significance of 0.000 < 0.5. Thus, Ho1 is rejected and Ha1 is accepted, then there is also an influence between the Physical Work Environment (X2) on Employee Performance (Y) at PT. Tunas Lima Warna South Tangerang, this can be seen from the results of the t test with a value of tcount > ttable (11.520 > 1.999), this is also proven by a significance of 0.000 < 0.05, thus Ho2 is rejected and Ha2 is accepted, and thirdly there is an influence between Work Discipline (X1) and Physical Work Environment (X2) on Employee Performance (Y) at PT. Tunas Lima Warna South Tangerang, this can be seen from the results of the F test with a value of Fcount > Ftable or (102.245 > 3.15), this is also reinforced by Sig < 0.05 or (0.000 < 0.05), thus Ho3 rejected and Ha3 accepted.